2017
DOI: 10.1186/s12888-017-1271-9
|View full text |Cite
|
Sign up to set email alerts
|

Mental health care and delivery system at Temeke hospital in Dar es Salaam, Tanzania

Abstract: BackgroundLow and middle income countries face many challenges in meeting mental health needs in their regions. Treatment of patients with mental disorders is inadequate in most of these countries and majority of individuals with severe mental disorders remain untreated. The bad news is that mental health problems in these countries are on the rise due to socioeconomic challenges being faced. Regardless of guidelines and directives provided by WHO for organizing mental health services, these countries continue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
1
25
0
1
Order By: Relevance
“…Preceding studies indicated that geographical accessibility limits especially in sub-Saharan African countries are an important barrier that hinders health-seeking for patients with mental disorders since this barrier increases privation and delay for seeking mental health services. These findings are also in the same vein with the previous studies conducted in Nigeria, Ethiopia, and South Africa where different systems of treating patients are applied (Abdulmalik and Sale, 2012;Jack-Ide and Uys, 2013;Ambikile and Iseselo, 2017;Musyimi et al, 2017). Additionally, financial strains limit their access to mental health services since the cost of some medications such as antipsychotic drugs is too much for them to shoulder on a long term.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Preceding studies indicated that geographical accessibility limits especially in sub-Saharan African countries are an important barrier that hinders health-seeking for patients with mental disorders since this barrier increases privation and delay for seeking mental health services. These findings are also in the same vein with the previous studies conducted in Nigeria, Ethiopia, and South Africa where different systems of treating patients are applied (Abdulmalik and Sale, 2012;Jack-Ide and Uys, 2013;Ambikile and Iseselo, 2017;Musyimi et al, 2017). Additionally, financial strains limit their access to mental health services since the cost of some medications such as antipsychotic drugs is too much for them to shoulder on a long term.…”
Section: Discussionsupporting
confidence: 80%
“…A research carried out in Ethiopia revealed that the main impediments to non-adherence to mental health services are that the mentally ill people denied taking mental health services because of thinking that they would get better later and that they also want to solve their mental problems without seeking health care from mental health providers; lack of medical infrastructures; negative attitudes of healthcare providers toward mentally ill patients; and preference to get alternative forms of mental health services (Wakida et al, 2018;Negash et al, 2020). So, mental disorders affect hundreds of millions of people and if left untreated create enormous suffering, disability, and economic loss (Moses et al, 2011;Ambikile and Iseselo, 2017). Further, prevailing public-health priority agenda and its effect on funding were the other barriers that weaken the mental health services.…”
Section: Introductionmentioning
confidence: 99%
“…The poor condition of mental healthcare facilities in South Africa is attributed to decades of underfunding, which results in dilapidated buildings unfit for use (Van Rooyen et al 2019 :2). Even though there is insufficient evidence to suggest that the physical environment enhances mental treatment outcomes, the findings of a study conducted in Tanzania has revealed that a conducive environment assists patients to recover, as it is considered a pure therapeutic environment (Ambikile & Iseselo 2017 :17). Therefore, governments in developing countries, including South Africa, should strive to prioritise mental health in order to improve treatment outcomes (Sunkel & Viljoen 2017 :15).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of people with mental illness remains untreated or seeks traditional treatment particularly in low-income countries [2,3]. Although some programs to provide services for mental illness at primary care level have been developed in low-income countries, these are generally limited because of poor integration of mental health into primary health care and inadequate resources [4][5][6].…”
Section: Introductionmentioning
confidence: 99%